Dynamic recrystallization of Zr-1Sn-0.3Nb alloy during hot compression. Issue 1 (July 2015) - Luan, B F; Zeng, Q H; Zeng, W; Liu, Q
Abstract: In this paper, using a hot-rolled and recrystallized Zr-1Sn-0.3Nb alloy sheet, five strain levels (10, 20, 30, 45 and 60%) of uniaxial compression experiments were performed at 700 o C with a strain rate of 0.001s -1 using a Gleeble 1500D thermal simulator. The morphologies, distributions and misorientations of the grain boundaries at different strains were characterized by an electron backscatter diffraction (EBSD) technique. The EBSD maps indicated that dynamic recrystallization occurred during the high-temperature deformation. The processes, namely, grain boundary bulging, strain induced subboundaries around the bulged grain boundaries and their transformation from low misorientation to high misorientation, were considered as the formation mechanisms of recrystallized grains. At the early stage of deformation, low angle boundaries (LABs) formed in grains, the original grain boundaries become serrated, and LABs formed around the serrated boundaries. With increasing strain, the LABs transformed into high angle boundaries (HABs), leading to nucleation of new grains.